Efforts to Increase the Potential of Sate Klatak Culinary Tourism in Bantul Regency - Vicki Dwi Purnomo; Budi Agus Riswandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Klatak satay is a unique satay and can only be found in Yogyakarta. The klatak satay, typical of Bantul Regency, is made from chunks of goat meat skewered with an iron rod. The meat is covered in a special simple concoction of spices such as garlic and salt. After that, satay grilled over charcoal is a culinary variation that is present in the midst of a culture in Bantul Regency. The author conducted qualitative research with a descriptive approach that aims to explore data related to community strategies in developing sate klatak culinary tourism in Bantul Regency. The informants in this study are visitors, sellers, and the local government. Collecting data in this study using three ways, namely, observation, interviews, and documentation. The results of the research from the trader's strategy in developing culinary satay klatak, which is a creative strategy by finding promoting ideas on social media, showing the advantages of oyster products based on arts and crafts, and highlighting tourism based on natural beauty. The impact of the roasted oyster seller strategy in Bantul Regency is the economic impact.